ANISTIZINNI SALITSIL VA 4-NITROBENZALDEGIDLAR BILAN REAKSIYASI - Islomov , Abbos; Sapayev , Frunza; Xoliqov , Tursunali (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Currently, the paint and varnish industry is developing in the world, and people's need for paints is increasing. Schiff bases are widely used in the pharmaceutical field, for example, they are formed with esters of 4-minobenzoic acids (fluoxetine, atropine, ethacrynic acid, trihexyphenidyl, procyclidine, ranitidine, biperiden). Schiff bases are also used in the food industry.